THE RECLAIMING CUBAN CULTURAL IDENTITY WHILE LIVING AS A CUBAN DIASPORA IN AMERICA AS DEPICTED IN CAMILA CABELLO “HAVANA” - Chandra, Tan Michael (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2019)
Question of identity remains one of the most important and debatable concept in the world of postcolonial theory especially when it is related to cultural identity of the diaspora. As culture is intertwined with place of origin, diasporic community often experience difficulty to identity themselves as they are located outside their culture of origin.By using Hall’s Cultural Identity, Bhabha’s Hybridity, and Historical Biographical approach, this paper shall dissect such notion of reclaiming the diasporic’s own culture as depicted in Camila Cabello’s most famous song “Havana.” Upon closer scrutiny, what at first glance considered as a simple love song underlines the cultural notion behind it. As the singer and songwriter is Cuban, Cabello expresses a theme of longing and stake a claim of Cuban cultural identity in the character of the song despite being offered a life in America. This perspective is highlighted through essay from Cabello herself, which notes the notion of cultural exchange and the life of the immigrants.